Composite coated cutting tool and method of making and use thereof
Patent Information
- Application Number
- CN202611479222.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-22
- Publication Date
- 2026-10-27
AI Technical Summary
但该类材料切削加工难度较高,因此对切削刀具的综合性能提出了严苛要求
Smart Images

Figure CN122979848A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of surface coating technology, and more specifically, to composite coated cutting tools, their preparation methods, and applications. Background Technology
[0002] Materials such as titanium alloys (e.g., Ti-6Al-4V) and high-temperature alloys (e.g., Inconel 718) are widely used in aerospace engines, gas turbines, and orthopedic implants due to their high specific strength, excellent corrosion resistance, and high-temperature performance. However, these materials are difficult to machine, thus placing stringent requirements on the overall performance of cutting tools.
[0003] It should be noted that the above statements are only used to provide background information related to this application and do not necessarily constitute prior art. Summary of the Invention
[0004] In a first aspect, this application provides a composite coated cutting tool, comprising a substrate and a composite coating located on at least one side of the substrate; wherein the composite coating comprises: an adhesive layer; the adhesive layer being located on at least one side of the substrate; a transition layer; the transition layer being located on the side of the adhesive layer away from the substrate; and a stress buffer layer; the stress buffer layer being located on the side of the transition layer away from the adhesive layer; the stress buffer layer comprising Al x Nb 1-x N, 0.4≤x≤0.6; functional layer; the functional layer is located on the side of the stress buffer layer away from the transition layer; the functional layer comprises N unit layers, N≥2; the unit layer comprises a first sub-layer and a second sub-layer; the first sub-layer comprises Al a Nb b B 1-a-b N, 0.4≤a≤0.6, 0.3≤b≤0.55, 1-ab>0; the second sub-layer includes Al c Nb d W 1-c-d N, 0.4≤c≤0.6, 0.3≤d≤0.55, 1-cd>0; surface layer; the surface layer is located on the side of the functional layer away from the stress buffer layer; the surface layer includes Al e Nb f B 1-e-f N, 0.4≤e≤0.6, 0.3≤f≤0.55, 1-ef>0.
[0005] First, the stress buffer layer, functional layer and surface layer of this application all include a lattice framework with AlNbN as the core. The AlNbN lattice framework has the following advantages: (1) The AlNbN lattice framework has high hardness, which can meet the cutting requirements of titanium alloys or high temperature alloys; (2) Metal Nb has excellent high temperature chemical stability. Even in high temperature environments above 900℃, it is difficult to generate volatile oxides, which can effectively improve the heat resistance limit of the tool composite coating; (3) The AlNbN lattice framework is conducive to improving high temperature stability, which can further improve the heat resistance limit of the tool composite coating; (4) AlNbN has low chemical affinity with titanium alloys or high temperature alloys, which can effectively reduce the impact on the surface quality of the machined workpiece; (5) By controlling the atomic stoichiometric ratio of element Al to element Nb in the AlNbN lattice framework within the aforementioned range, not only can a stable solid solution structure be formed, but the high temperature anti-sticking property of the composite coating can also be effectively maintained.
[0006] Secondly, in the first sublayer of the functional layer, the AlNbN lattice framework doped with boron (B) forms an amorphous BN phase, which reduces the friction coefficient and improves the self-lubricating properties of the composite coating, thereby effectively reducing the machining difficulty. In the second sublayer of the functional layer, the W (W) doped into the AlNbN lattice framework produces a solid solution strengthening effect, which effectively improves the hardness and oxidation barrier of the composite coating, further meeting the machining requirements of titanium alloys or high-temperature alloys. Simultaneously, the layered design of the first and second sublayers reduces the competitive segregation between B and W elements, minimizing their impact on the composite coating's performance. The stress buffer layer releases stress in the composite coating, effectively improving the interfacial bonding strength between the layers. The surface layer, with its AlNbN lattice framework doped with B forming an amorphous BN phase, possesses a low friction coefficient and self-lubricating properties, further reducing the machining difficulty and improving the quality of the machined workpiece.
[0007] Therefore, the surface coating of the composite coated tool of this application has high hardness, high temperature stability, low chemical affinity with titanium alloys or high temperature alloys, low surface friction coefficient, and high interfacial bonding strength, which can meet the cutting requirements of titanium alloys or high temperature alloys and improve the quality of machined workpieces.
[0008] In some implementations, one or more of the following conditions are satisfied: 0.01≤1-ab≤0.1; 0.01≤1-cd≤0.1; 0.01≤1-ef≤0.1.
[0009] In some embodiments, the unit layer satisfies one or more of the following conditions: the thickness of a single unit layer is 10nm-50nm; the thickness of the first sub-layer is 5nm-25nm; the thickness of the second sub-layer is 5nm-25nm; counting from the side of the functional layer closest to the stress buffer layer towards the side closest to the surface layer, the thickness of the second sub-layer in the nth unit layer is greater than the thickness of the second sub-layer in the (n+1)th unit layer, where n+1≤N, and n and N are independent positive integers; counting from the side of the functional layer closest to the stress buffer layer towards the side closest to the surface layer, the ratio of the thickness of the first sub-layer in the nth unit layer to the thickness of the first sub-layer in the (n+1)th unit layer is 1:(0.95-1.05); and N is greater than or equal to 6 and less than or equal to 200.
[0010] In some embodiments, the stress buffer layer has a face-centered cubic crystal structure.
[0011] In some embodiments, one or two of the following conditions are met: the average grain size of the grains in the stress buffer layer is greater than the average grain size of the grains in the functional layer, which is greater than the average grain size of the grains in the surface layer; the Vickers hardness of the stress buffer layer is less than the Vickers hardness of the functional layer, which is less than the Vickers hardness of the surface layer.
[0012] In some embodiments, one or more of the following conditions are met: the average grain size of the grains in the stress buffer layer is 30nm-200nm; the average grain size of the grains in the functional layer is 5nm-50nm; the average grain size of the grains in the surface layer is 10nm-30nm; the Vickers hardness of the stress buffer layer is 24GPa-32GPa; the Vickers hardness of the functional layer is 26GPa-36GPa; and the Vickers hardness of the surface layer is 27GPa-38GPa.
[0013] In some embodiments, one or more of the following conditions are met: the thickness of the stress buffer layer is 0.2 μm-1.0 μm; the thickness of the functional layer is 0.5 μm-3.0 μm; and the thickness of the surface layer is 0.5 μm-2.0 μm.
[0014] In some embodiments, the adhesive layer satisfies one or two of the following conditions: the adhesive layer comprises titanium metal; the thickness of the adhesive layer is 0.05 μm-0.1 μm.
[0015] In some embodiments, the transition layer satisfies one or two of the following conditions: the transition layer comprises TiN; the thickness of the transition layer is 0.1 μm-0.2 μm.
[0016] In some embodiments, the thickness of the composite coating is 1.5 μm to 5.0 μm.
[0017] In some embodiments, the substrate satisfies one or more of the following conditions: the substrate comprises one or more of cemented carbide, cermet, cubic boron nitride sintered body, and high-speed steel; the substrate comprises tungsten carbide cemented carbide doped with cobalt metal, wherein, based on the mass of the tungsten carbide cemented carbide doped with cobalt metal, the mass percentage of cobalt element is 6%-12%.
[0018] In a second aspect, this application provides a method for preparing a composite coated cutting tool, comprising: depositing a composite coating on at least one side of a substrate; The deposited composite coating includes: An adhesive layer is deposited on at least one side of the substrate; A transition layer is deposited on the side of the adhesive layer away from the substrate; A first deposition process is performed on the side of the transition layer away from the adhesive layer to obtain a stress buffer layer; A second deposition process is performed on the side of the stress buffer layer away from the transition layer to obtain a functional layer containing N unit layers, where N≥2; A third deposition process is performed on the side of the functional layer away from the stress buffer layer to obtain the surface layer; The stress buffer layer includes Al x Nb 1-x N, 0.4 ≤ x ≤ 0.6; The unit layer in the functional layer includes a first sub-layer and a second sub-layer; the first sub-layer includes A1 a Nb b B 1-a-b N, 0.4≤a≤0.6, 0.3≤b≤0.55, 1-ab>0; the second sub-layer includes Al c Nb d W 1-c-d N, 0.4≤c≤0.6, 0.3≤d≤0.55, 1-cd>0; The surface layer includes Al e Nb f B 1-e-f N, 0.4≤e≤0.6, 0.3≤f≤0.55, 1-ef>0.
[0019] In some embodiments, the method for depositing the composite coating includes physical vapor deposition; the physical vapor deposition method includes pulsed magnetron sputtering, wherein the average power of the pulsed magnetron sputtering is 1000W-10000W.
[0020] In some embodiments, the second deposition process satisfies one or more of the following conditions: The temperature of the substrate is 600℃-750℃; The bias voltage of the substrate is -60V to -120V; The target material for depositing the first sublayer includes an AlNbB alloy; in the AlNbB alloy, the atomic ratio of Al atoms, Nb atoms, and B atoms is (0.4-0.6):(0.3-0.55):(0.01-0.1). The average power for depositing the first sublayer is 2000W-6000W; The target material for depositing the second sublayer includes an AlNbW alloy; in the AlNbW alloy, the atomic ratio of Al atoms, Nb atoms, and W atoms is (0.4-0.6):(0.3-0.55):(0.01-0.1). The average power for depositing the second sublayer was 2000W-6000W; The second deposition process further includes introducing nitrogen gas at a flow rate of 200 sccm-500 sccm; The working pressure for the second deposition treatment is 0.4 Pa - 0.8 Pa; Counting from the side of the functional layer closest to the stress buffer layer towards the side closest to the surface layer, the average power of the second sublayer in the nth unit layer is greater than the average power of the second sublayer in the (n+1)th unit layer; where n+1≤N, and n and N are independent positive integers; Counting from the side of the functional layer closest to the stress buffer layer toward the side closest to the surface layer, the ratio of the average power of the first sublayer in the nth unit layer to the average power of the first sublayer in the (n+1)th unit layer is 1:(0.95-1.05).
[0021] In some implementations, the first deposition process satisfies one or more of the following conditions: The temperature of the substrate is 600℃-750℃; The bias voltage of the substrate is -40V to -100V; The target material for depositing the stress buffer layer includes an AlNb alloy; in the AlNb alloy, the atomic ratio of Al atoms to Nb atoms is (0.4-0.6):(0.6-0.4); The average power of the first deposition process is 1000W-6000W; During the first deposition process, the power gradually increases from 1000W to h, where h ranges from 2000W to 6000W. The first deposition process further includes introducing nitrogen gas at a flow rate of 200 sccm-500 sccm; The working pressure of the first deposition treatment is 0.4 Pa to 0.8 Pa.
[0022] In some embodiments, the third deposition process satisfies one or more of the following conditions: The temperature of the substrate is 600℃-750℃; The bias voltage of the substrate is -80V to -140V; The target material for depositing the surface layer includes an AlNbB alloy; in the AlNbB alloy, the atomic ratio of Al atoms, Nb atoms, and B atoms is (0.4-0.6):(0.3-0.55):(0.01-0.1). The average power of the third deposition process is 3000W-6000W; The third deposition process also includes introducing nitrogen gas at a flow rate of 200 sccm-500 sccm; The working pressure for the third deposition process is 0.4 Pa to 0.8 Pa.
[0023] In some embodiments, the method further includes performing a fourth deposition process on at least one side of the substrate to obtain the adhesive layer, the adhesive layer comprising titanium metal; The fourth deposition process satisfies one or more of the following conditions: The temperature of the substrate is 600℃-750℃; The bias voltage of the substrate is -150V to -200V; The target material for depositing the adhesive layer includes titanium metal; The average power of the fourth deposition process is 6000W-8000W; The working pressure for the fourth deposition process is 0.4 Pa to 0.8 Pa. Before the fourth deposition process, the substrate is further cleaned; the cleaning process includes, in sequence, sandblasting, water washing, and glow discharge cleaning.
[0024] In some embodiments, the method further includes performing a fifth deposition process on the side of the adhesive layer away from the substrate to obtain the transition layer, the transition layer comprising TiN; The fifth deposition process satisfies one or more of the following conditions: The temperature of the substrate is 600℃-750℃; The bias voltage of the substrate is -100V to -150V; The target material for depositing the transition layer includes titanium metal; The average power of the fifth deposition process is 6000W-8000W; The fifth deposition process also includes introducing nitrogen gas at a flow rate of 200 sccm-300 sccm; The working pressure for the fifth deposition treatment is 0.4 Pa to 0.8 Pa.
[0025] In a third aspect, this application provides the application of a composite coated tool according to the first aspect of this application or a composite coated tool prepared by the method of the second aspect of this application in the cutting of titanium alloys and / or high-temperature alloys.
[0026] In some embodiments, one or two of the following conditions are met: the titanium alloy includes one or two of TC4 and TC18; the high-temperature alloy includes one or two of nickel-based high-temperature alloys and iron-based high-temperature alloys. Attached Figure Description
[0027] Figure 1 This is a schematic diagram of the structure of a composite coated cutting tool according to one embodiment of this application.
[0028] Explanation of reference numerals in the attached figures: 1. Substrate; 2. Composite coating; 21. Adhesive layer; 22. Transition layer; 23. Stress buffer layer; 24. Functional layer; 241. First sublayer; 242. Second sublayer; 25. Surface layer. Detailed Implementation
[0029] The embodiments of this application are disclosed in detail below. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of actually identical structures may be omitted. This is to avoid making the following description unnecessarily lengthy and to facilitate understanding by those skilled in the art.
[0030] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is also expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0031] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0032] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0033] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used in this application is for the purpose of describing particular embodiments only and is not intended to limit this application; unless otherwise stated, the values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (e.g., they can be tested according to the methods given in the embodiments of this application).
[0034] In the description of this application, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. "First feature" and "second feature" may include one or more of the indicated feature.
[0035] In the description of this application, "A and / or B" can include any of the cases of A alone, B alone, or A and B, where A and B are merely examples and can be any technical feature connected by "and / or" in this application.
[0036] For cutting tools that cut titanium alloys or high-temperature alloys, in addition to the tool substrate, the surface coating of the tool is also one of the important factors affecting the performance of the cutting tool.
[0037] However, on the one hand, titanium alloys and high-temperature alloys have low thermal conductivity. During the cutting process, the cutting heat generated is concentrated in a very small area of the "tool-chip" contact zone, which can cause the tool tip temperature to reach 800℃-1000℃, far exceeding the heat resistance limit of conventional tool surface coatings. This can easily lead to damage to the tool surface coating and a shorter service life.
[0038] On the other hand, when the tip temperature exceeds 600°C, metallic titanium will undergo intense diffusion and chemical bonding with conventional tool coating materials, such as Ti-containing nitride coatings, resulting in "crescent-shaped" wear and built-up edge on the tool surface, which seriously affects the surface quality of the machined workpiece.
[0039] Based on this, in a first aspect, this application provides a composite coated cutting tool, including a substrate and a composite coating located on at least one side of the substrate; The composite coating includes: Adhesive layer; the adhesive layer is located on at least one side of the substrate; Transition layer; the transition layer is located on the side of the adhesive layer away from the substrate; Stress buffer layer; the stress buffer layer is located on the side of the transition layer away from the adhesive layer; the stress buffer layer includes Al x Nb 1-x N, 0.4 ≤ x ≤ 0.6; Functional layer; the functional layer is located on the side of the stress buffer layer away from the transition layer; the functional layer comprises N unit layers, N≥2; each unit layer comprises a first sub-layer and a second sub-layer; the first sub-layer comprises A1 a Nb b B 1-a- b N, 0.4≤a≤0.6, 0.3≤b≤0.55, 1-ab>0; the second sub-layer includes Al c Nb d W 1-c-d N, 0.4≤c≤0.6, 0.3≤d≤0.55, 1-cd>0; Surface layer; the surface layer is located on the side of the functional layer away from the stress buffer layer; the surface layer includes Al e Nb f B 1-e-f N, 0.4≤e≤0.6, 0.3≤f≤0.55, 1-ef>0.
[0040] First, the stress buffer layer, functional layer and surface layer of this application all include a lattice framework with AlNbN as the core. The AlNbN lattice framework has the following advantages: (1) The AlNbN lattice framework has high hardness, which can meet the cutting requirements of titanium alloys or high temperature alloys; (2) Metal Nb has excellent high temperature chemical stability. Even in high temperature environments above 900℃, it is difficult to generate volatile oxides, which can effectively improve the heat resistance limit of the tool composite coating; (3) The AlNbN lattice framework is conducive to improving high temperature stability, which can further improve the heat resistance limit of the tool composite coating; (4) AlNbN has low chemical affinity with titanium alloys or high temperature alloys, which can effectively reduce the impact on the surface quality of the machined workpiece; (5) By controlling the atomic stoichiometric ratio of element Al to element Nb in the AlNbN lattice framework within the aforementioned range, not only can a stable solid solution structure be formed, but the high temperature anti-sticking property of the composite coating can also be effectively maintained.
[0041] Secondly, in the first sublayer of the functional layer, the AlNbN lattice framework doped with boron (B) forms an amorphous BN phase, which reduces the friction coefficient and improves the self-lubricating properties of the composite coating, thereby effectively reducing the machining difficulty. In the second sublayer of the functional layer, the W (W) doped into the AlNbN lattice framework produces a solid solution strengthening effect, which effectively improves the hardness and oxidation barrier of the composite coating, further meeting the machining requirements of titanium alloys or high-temperature alloys. Simultaneously, the layered design of the first and second sublayers reduces the competitive segregation between B and W elements, minimizing their impact on the composite coating's performance. The stress buffer layer releases stress in the composite coating, effectively improving the interfacial bonding strength between the layers. The surface layer, with its AlNbN lattice framework doped with B forming an amorphous BN phase, possesses a low friction coefficient and self-lubricating properties, further reducing the machining difficulty and improving the quality of the machined workpiece.
[0042] Therefore, the surface coating of the composite coated tool of this application has high hardness, high temperature stability, low chemical affinity with titanium alloys or high temperature alloys, low surface friction coefficient, and high interfacial bonding strength, which can meet the cutting requirements of titanium alloys or high temperature alloys and improve the quality of machined workpieces.
[0043] As an example, x can be 0.4, 0.42, 0.44, 0.46, 0.48, 0.5, 0.52, 0.54, 0.56, 0.58, 0.6, etc., or a range consisting of any two of the above values.
[0044] As an example, 'a' can be 0.4, 0.42, 0.44, 0.46, 0.48, 0.5, 0.52, 0.54, 0.56, 0.58, 0.6, etc., or a range consisting of any two of the above values.
[0045] As an example, b can be 0.3, 0.33, 0.35, 0.37, 0.39, 0.41, 0.43, 0.45, 0.47, 0.49, 0.51, 0.53, 0.55, etc., or a range consisting of any two of the above values.
[0046] As an example, c can be 0.4, 0.42, 0.44, 0.46, 0.48, 0.5, 0.52, 0.54, 0.56, 0.58, 0.6, etc., or a range consisting of any two of the above values.
[0047] As an example, d can be 0.3, 0.33, 0.35, 0.37, 0.39, 0.41, 0.43, 0.45, 0.47, 0.49, 0.51, 0.53, 0.55, etc., or a range consisting of any two of the above values.
[0048] As an example, e can be 0.4, 0.42, 0.44, 0.46, 0.48, 0.5, 0.52, 0.54, 0.56, 0.58, 0.6, etc., or a range consisting of any two of the above values.
[0049] As an example, f can be 0.3, 0.33, 0.35, 0.37, 0.39, 0.41, 0.43, 0.45, 0.47, 0.49, 0.51, 0.53, 0.55, etc., or a range consisting of any two of the above values.
[0050] In some implementations, 0.01 ≤ 1 - ab ≤ 0.1.
[0051] Therefore, controlling the atomic stoichiometry of element B within the aforementioned range can not only increase the content of amorphous BN phase in the first sublayer of the functional layer to effectively reduce the friction coefficient and improve self-lubrication, but also reduce the impact on the hardness of the composite coating.
[0052] In some implementations, 0.01 ≤ 1 - cd ≤ 0.1.
[0053] Therefore, by controlling the atomic stoichiometric coefficient of W within the aforementioned range, the solid solution strengthening effect of W can effectively improve the hardness and oxidation resistance of the second sublayer; at the same time, it can also control the content of brittle W2N phase in the second sublayer to reduce its impact on the hardness of the composite coating.
[0054] In some implementations, 0.01 ≤ 1-ef ≤ 0.1.
[0055] Therefore, controlling the atomic stoichiometry of element B within the aforementioned range can not only increase the content of amorphous BN phase in the surface layer to effectively reduce the friction coefficient and improve self-lubrication, but also reduce the impact on the hardness of the composite coating.
[0056] As an example, 1-ab can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, etc., or a range consisting of any two of the above values.
[0057] As an example, 1-cd can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, etc., or a range consisting of any two of the above values.
[0058] As an example, 1-ef can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, etc., or a range consisting of any two of the above values.
[0059] The composition and structure of composite coated cutting tools will be further explained below.
[0060] [Matrix]: In some embodiments, the composite coated tool includes a substrate.
[0061] The substrate is the main material of the cutting tool, used to bear the load, support the composite coating, and transmit cutting forces.
[0062] In some embodiments, the matrix includes one or more of cemented carbide, cermet, cubic boron nitride sintered body, and high-speed steel.
[0063] Therefore, the matrix materials within the aforementioned range have high hardness, which can meet the hardness requirements for cutting titanium alloys or high-temperature alloys.
[0064] As an example, cemented carbide can include WC-Co cemented carbide; cermet can include titanium-based cermet, etc.
[0065] In some embodiments, the matrix comprises a tungsten carbide cemented carbide doped with cobalt metal, wherein the mass percentage of cobalt is 6%-12% based on the mass of the cobalt-doped tungsten carbide.
[0066] Therefore, tungsten carbide cemented carbide doped with cobalt metal has both high hardness and toughness; at the same time, by controlling the mass ratio of cobalt in tungsten carbide cemented carbide within the aforementioned range, the impact on the hardness of the matrix can be reduced while improving the toughness of the matrix.
[0067] As an example, based on the mass of the tungsten carbide cemented carbide doped with cobalt metal, the mass percentage of cobalt can be 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, etc., or a range consisting of any two of the above values.
[0068] [Composite coating]: In some embodiments, the composite coating is located on at least one side of the substrate.
[0069] Therefore, the composite coating of this application has advantages such as high hardness, high temperature stability, low chemical affinity with titanium alloys or high temperature alloys, low surface friction coefficient, and high interfacial bonding strength; at the same time, the substrate has advantages of high hardness and high toughness, thereby improving the overall performance of the cutting tool to meet the cutting requirements of titanium alloys or high temperature alloys.
[0070] In some embodiments, the thickness of the composite coating is 1.5 μm to 5.0 μm.
[0071] Therefore, controlling the thickness of the composite coating within the aforementioned range can not only meet cutting requirements and extend service life, but also effectively control the internal stress of the composite coating, thereby reducing the risk of composite coating damage.
[0072] As an example, the thickness of the composite coating can be 1.5μm, 2.0μm, 2.5μm, 3.0μm, 3.5μm, 4.0μm, 4.5μm, 5.0μm, or a range of any two of the above values.
[0073] [Stress buffer layer]: In some embodiments, the stress buffer layer is located on the side of the transition layer away from the adhesive layer; the stress buffer layer includes Al. x Nb 1-x N, 0.4≤x≤0.6.
[0074] Therefore, the stress buffer layer satisfies all the advantages of the AlNbN lattice framework. At the same time, the stress buffer layer can release the stress in the composite coating to effectively improve the interfacial bonding strength of each layer in the composite coating.
[0075] In some embodiments, the stress buffer layer has a face-centered cubic crystal structure.
[0076] Therefore, the face-centered cubic crystal structure not only facilitates stress release but also promotes the growth of functional layer grains and enhances the bonding strength between the functional layer and the transition layer.
[0077] In some embodiments, the thickness of the stress buffer layer is 0.2 μm to 1.0 μm.
[0078] Therefore, controlling the thickness of the stress buffer layer within the aforementioned range can not only leverage the advantages of the stress buffer layer to meet cutting requirements and extend service life, but also effectively control the internal stress of the stress buffer layer to reduce the risk of composite coating damage.
[0079] As an example, the thickness of the stress buffer layer can be 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm, or a range consisting of any two of the above values.
[0080] [Functional Layer]: In some embodiments, the functional layer is located on the side of the stress buffer layer away from the transition layer; the functional layer comprises N unit layers, N≥2; each unit layer comprises a first sub-layer and a second sub-layer; the first sub-layer comprises A1 a Nb b B 1-a-b N, 0.4≤a≤0.6, 0.3≤b≤0.55, 1-ab>0; the second sub-layer includes Al c Nb d W 1-c-d N, 0.4≤c≤0.6, 0.3≤d≤0.55, 1-cd>0.
[0081] Thus, the functional layer satisfies all the advantages of the AlNbN lattice framework. At the same time, the functional layer also has a low coefficient of friction and self-lubrication, high hardness and good high-temperature oxidation resistance.
[0082] It is understandable that either the first sublayer or the second sublayer can be deposited first on the surface of the stress buffer layer. That is, the preferred placement of either the first or second sublayer on the surface of the stress buffer layer has a relatively small impact on the performance of the composite coating.
[0083] In some embodiments, the thickness of the functional layer is 0.5 μm to 3.0 μm.
[0084] Therefore, controlling the thickness of the functional layer within the aforementioned range can not only leverage the advantages of the functional layer to meet cutting requirements and improve the quality of machined workpieces, but also effectively control the internal stress of the functional layer to reduce the risk of damage to the composite coating.
[0085] As an example, the thickness of the functional layer can be 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2.0μm, 2.1μm, 2.2μm, 2.3μm, 2.4μm, 2.5μm, 2.6μm, 2.7μm, 2.8μm, 2.9μm, 3.0μm, or a range consisting of any two of the above values.
[0086] In some implementations, the thickness of a single unit layer is 10 nm to 50 nm.
[0087] As an example, the thickness of a single unit layer can be 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, etc., or a range consisting of any two of the above values.
[0088] In some implementations, N is greater than or equal to 6 and less than or equal to 200.
[0089] As an example, N can be 6, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 120, 140, 160, 180, 200, etc., or a range consisting of any two of the above values.
[0090] In some embodiments, counting from the side of the functional layer closest to the stress buffer layer toward the side closest to the surface layer, the thickness of the second sublayer in the nth unit layer is greater than the thickness of the second sublayer in the (n+1)th unit layer, where n+1≤N, and n and N are independent positive integers.
[0091] Therefore, the thickness of the second sublayer in the functional layer is designed in a gradient manner. The second sublayer on the side closer to the stress buffer layer has a larger thickness, which can provide the functional layer with excellent hardness and oxidation resistance; the second sublayer on the side closer to the surface layer has a smaller thickness, which can reduce the impact on the coefficient of friction and anti-stick properties.
[0092] In some implementations, the thickness of the second sublayer is 5nm-25nm.
[0093] It is understood that the thickness of the second sublayer closest to the stress buffer layer can be up to 25 nm; the thickness of the second sublayer closest to the surface layer can be as low as 5 nm.
[0094] As an example, the thickness of the second sublayer can be 5nm, 7nm, 9nm, 11nm, 13nm, 15nm, 17nm, 19nm, 21nm, 23nm, 25nm, etc., or a range consisting of any two of the above values.
[0095] In some embodiments, counting from the side of the functional layer closest to the stress buffer layer toward the side closest to the surface layer, the ratio of the thickness of the first sublayer in the nth unit layer to the thickness of the first sublayer in the (n+1)th unit layer is 1:(0.95-1.05).
[0096] Therefore, the thickness variation of the first sublayer in the functional layer is small, which can effectively ensure the low coefficient of friction and self-lubrication of the functional layer.
[0097] As an example, counting from the side of the functional layer closest to the stress buffer layer towards the side closest to the surface layer, the ratio of the thickness of the first sub-layer in the nth unit layer to the thickness of the first sub-layer in the (n+1)th unit layer can be 1:0.95, 1:0.96, 1:0.97, 1:0.98, 1:0.99, 1:1.0, 1:1.01, 1:1.02, 1:1.03, 1:1.04, 1:1.05, etc., or a range consisting of any two of the above values.
[0098] In some implementations, the thickness of the first sublayer is 5nm-25nm; As an example, the thickness of the first sublayer can be 5nm, 7nm, 9nm, 11nm, 13nm, 15nm, 17nm, 19nm, 21nm, 23nm, 25nm, etc., or a range consisting of any two of the above values.
[0099] [surface layer]: In some embodiments, the surface layer is located on the side of the functional layer away from the stress-relief layer; the surface layer includes Al. e Nb f B 1-e-f N, 0.4≤e≤0.6, 0.3≤f≤0.55, 1-ef>0.
[0100] Therefore, the surface layer satisfies all the advantages of the AlNbN lattice framework. At the same time, the surface layer also has a low coefficient of friction and self-lubricating properties, which can further reduce the cutting difficulty and improve the quality of the machined workpiece.
[0101] In some embodiments, the thickness of the surface layer is 0.5 μm to 2.0 μm.
[0102] Therefore, controlling the thickness of the surface layer within the aforementioned range can not only leverage the advantages of the surface layer to meet cutting requirements and improve the quality of machined workpieces, but also effectively control the internal stress of the surface layer to reduce the risk of damage to the composite coating.
[0103] As an example, the thickness of the surface layer can be 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2.0μm, etc., or a range consisting of any two of the above values.
[0104] In some embodiments, the average grain size of the grains in the stress buffer layer is greater than the average grain size of the grains in the functional layer, which is greater than the average grain size of the grains in the surface layer.
[0105] It is understandable that in the composite coating of this application, under the same volume conditions, the smaller the average grain size, the higher the volume ratio of grain boundaries; the increase in the volume ratio of grain boundaries will hinder dislocation slip and plastic deformation, but its macroscopic hardness will be improved.
[0106] Therefore, from the surface of the composite coating closest to the substrate to the surface furthest from the substrate, the grain size of each layer in the composite coating gradually decreases, and the macroscopic hardness of each layer gradually increases along this direction. This results in the layer structure furthest from the substrate having higher hardness, which meets the cutting requirements of titanium alloys or high-temperature alloys. At the same time, it can effectively reduce the internal stress of the layer structure close to the substrate, thereby reducing the risk of the composite coating peeling off.
[0107] In some embodiments, the average grain size of the grains in the stress buffer layer is 30nm-200nm.
[0108] As an example, the average grain size of the grains in the stress buffer layer can be 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm, etc., or a range consisting of any two of the above values.
[0109] In some embodiments, the average grain size of the grains in the functional layer is 5nm-50nm.
[0110] In the embodiments of this application, the average grain size of the grains in the functional layer is taken as the average value of the grain size corresponding to the first sublayer and the second sublayer.
[0111] As an example, the average grain size of the grains in the functional layer can be 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, etc., or a range consisting of any two of the above values.
[0112] In some embodiments, the average grain size of the grains in the surface layer is 10 nm to 30 nm.
[0113] As an example, the average grain size of the grains in the surface layer can be 10nm, 15nm, 20nm, 25nm, 30nm, etc., or a range consisting of any two of the above values.
[0114] In some embodiments, the Vickers hardness of the stress buffer layer is less than the Vickers hardness of the functional layer, which in turn is less than the Vickers hardness of the surface layer.
[0115] Vickers hardness refers to the process of pressing a regular square pyramidal diamond indenter into the surface of a sample under a specified load, maintaining the load, removing the load, measuring the average length of the two diagonals of the indentation, and calculating the surface area of the indentation. Vickers hardness = test load / indentation surface area. That is, the higher the Vickers hardness value, the higher the hardness of the material.
[0116] Therefore, from the side of the composite coating closest to the substrate towards the side away from the substrate, the Vickers hardness of each layer in the composite coating gradually increases, so that the layer structure away from the substrate has higher hardness, which meets the cutting requirements of titanium alloys or high-temperature alloys; at the same time, it can effectively reduce the internal stress of the layer structure close to the substrate, thereby reducing the risk of composite coating peeling off.
[0117] In some embodiments, the Vickers hardness of the stress buffer layer is 24 GPa-32 GPa.
[0118] As an example, the Vickers hardness of the stress buffer layer can be 24GPa, 25GPa, 26GPa, 27GPa, 28GPa, 29GPa, 30GPa, 31GPa, 32GPa, or a range of any two of the above values.
[0119] In some embodiments, the Vickers hardness of the functional layer is 26 GPa-36 GPa.
[0120] As an example, the Vickers hardness of the functional layer can be 26GPa, 27GPa, 28GPa, 29GPa, 30GPa, 31GPa, 32GPa, 33GPa, 34GPa, 35GPa, 36GPa, etc., or a range consisting of any two of the above values.
[0121] In some embodiments, the Vickers hardness of the surface layer is 27 GPa-38 GPa.
[0122] As an example, the Vickers hardness of the surface can be 27GPa, 28GPa, 29GPa, 30GPa, 31GPa, 32GPa, 33GPa, 34GPa, 35GPa, 36GPa, 37GPa, 38GPa, etc., or a range consisting of any two of the above values.
[0123] [Adhesive layer]: In some embodiments, the adhesive layer is located between the substrate and the transition layer.
[0124] In some embodiments, the adhesive layer comprises titanium metal.
[0125] Therefore, the adhesive layer is used to enhance the bonding force between the composite coating and the substrate.
[0126] In some embodiments, the thickness of the adhesive layer is 0.05 μm to 0.1 μm.
[0127] Therefore, by controlling the thickness of the adhesive layer within the aforementioned range, the composite coating can be effectively bonded to the substrate, while also reducing the impact on the hardness of the composite coating.
[0128] As an example, the thickness of the adhesive layer can be 0.05μm, 0.055μm, 0.06μm, 0.065μm, 0.07μm, 0.075μm, 0.08μm, 0.085μm, 0.09μm, 0.095μm, 0.1μm, or a range of any two of the above values.
[0129] [Transition Layer]: In some embodiments, the transition layer is located between the adhesive layer and the stress buffer layer.
[0130] In some implementations, the transition layer comprises TiN.
[0131] Therefore, the transition layer can not only serve as a chemical barrier layer for the matrix, but also provide hardness support.
[0132] In some embodiments, the thickness of the transition layer is 0.1 μm to 0.2 μm.
[0133] Therefore, controlling the thickness of the transition layer within the aforementioned range can not only serve as a chemical barrier layer for the substrate, but also reduce the impact on the hardness of the composite coating.
[0134] As an example, the thickness of the transition layer can be 0.1μm, 0.11μm, 0.12μm, 0.13μm, 0.14μm, 0.15μm, 0.16μm, 0.17μm, 0.18μm, 0.19μm, 0.2μm, or a range consisting of any two of the above values.
[0135] In some embodiments, the composite coating sequentially comprises an adhesive layer, a transition layer, a stress buffer layer, a functional layer, and a surface layer.
[0136] As an example, such as Figure 1 The composite coated tool includes a substrate 1 and a composite coating 2 on one side surface of the substrate. From the side surface of the composite coating closest to the substrate towards the side surface furthest from the substrate, the composite coating sequentially includes an adhesive layer 21, a transition layer 22, a stress buffer layer 23, a functional layer 24, and a surface layer 25.
[0137] As an example, functional layer 24 includes a first sub-layer 241 and a second sub-layer 242, which are alternately arranged.
[0138] The composition of the binder, transition layer, stress buffer layer, functional layer, and surface layer in the composite coating can be tested using the following methods. As an example, argon ion polishing is used to prepare the tool sample, obtaining a cross-section of the composite coating in the thickness direction. This cross-section is then tested using scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS) to obtain information such as the composition and geometric thickness of each layer. Alternatively, X-ray photoelectron spectroscopy (XPS) can be used to deeply etch the composite coating of the tool to obtain elemental composition information along its thickness direction.
[0139] In a second aspect, this application provides a method for preparing a composite coated cutting tool, comprising: depositing a composite coating on at least one side of a substrate.
[0140] In some embodiments, the method for depositing the composite coating includes physical vapor deposition; the physical vapor deposition method includes pulsed magnetron sputtering, wherein the average power of the pulsed magnetron sputtering is 1000W-10000W.
[0141] This application employs high-power pulsed magnetron sputtering (HiPIMS) technology, utilizing its high plasma density (10⁻⁶ ppm). 18 m -3 -10 19 m -3 With high sputtering particle ionization rate (>90%), the deposited composite coating has a dense microstructure, low residual stress and excellent substrate adhesion.
[0142] As an example, the average power of the pulsed magnetron sputtering can be 1000W, 2000W, 3000W, 4000W, 5000W, 6000W, 7000W, 8000W, 9000W, 10000W, or a range of any two of the above values.
[0143] In some implementations, the working gas for pulsed magnetron sputtering includes argon.
[0144] In some embodiments, the deposition of the composite coating includes the following steps: S100, Deposit an adhesive layer on at least one side of the substrate.
[0145] S200, Deposit a transition layer on the side of the adhesive layer away from the substrate.
[0146] S300, A first deposition process is performed on the side of the transition layer away from the adhesive layer to obtain a stress buffer layer; the stress buffer layer includes Al x Nb 1-x N, 0.4≤x≤0.6.
[0147] In some implementations, the first deposition process satisfies one or more of the following conditions: The temperature of the substrate is 600℃-750℃; The bias voltage of the substrate is -40V to -100V; The target material for depositing the stress buffer layer includes an AlNb alloy; in the AlNb alloy, the atomic ratio of Al atoms to Nb atoms is (0.4-0.6):(0.6-0.4); The average power of the first deposition process is 1000W-6000W; During the first deposition process, the power gradually increases from 1000W to h, where h ranges from 2000W to 6000W. The first deposition process further includes introducing nitrogen gas at a flow rate of 200 sccm-500 sccm; The working pressure of the first deposition treatment is 0.4 Pa to 0.8 Pa.
[0148] Therefore, in the plasma environment, sputtered AlNb particles react with active nitrogen free radicals generated by nitrogen dissociation in the gas phase, thereby depositing a stress buffer layer; and by controlling the deposition conditions of the first deposition treatment within the aforementioned range, a stress buffer layer within the scope defined in this application can be obtained.
[0149] It is understood that during the first deposition process, the average power gradually increases from 1000W to 6000W, which can release the residual stress in the stress buffer layer through a gradient.
[0150] As an example, the temperature of the substrate can be 600℃, 620℃, 640℃, 660℃, 680℃, 700℃, 720℃, 740℃, 750℃, or a range of any two of the above values.
[0151] As an example, the bias voltage of the substrate can be -40V, -45V, -50V, -55V, -60V, -65V, -70V, -75V, -80V, -85V, -90V, -95V, -100V, or a range consisting of any two of the above values.
[0152] As an example, in the AlNb alloy, the atomic ratio of Al atoms to Nb atoms can be 0.4:0.6, 0.45:0.55, 0.5:0.5, 0.55:0.45, 0.6:0.4, or a range consisting of any two of the above values.
[0153] As an example, the average power of the first deposition process can be 1000W, 2000W, 3000W, 4000W, 5000W, 6000W, or a range consisting of any two of the above values.
[0154] As an example, h can be 2000W, 3000W, 4000W, 5000W, 6000W, etc., or a range consisting of any two of the above values.
[0155] As an example, the flow rate of nitrogen gas can be 200 sccm, 250 sccm, 300 sccm, 350 sccm, 400 sccm, 450 sccm, 500 sccm, etc., or a range consisting of any two of the above values.
[0156] As an example, the working pressure of the first deposition process can be 0.4 Pa, 0.45 Pa, 0.5 Pa, 0.55 Pa, 0.6 Pa, 0.65 Pa, 0.7 Pa, 0.75 Pa, 0.8 Pa, or a range consisting of any two of the above values.
[0157] S400, A second deposition process is performed on the side of the stress buffer layer away from the transition layer to obtain a functional layer containing N unit layers, where N≥2; the unit layers in the functional layer include a first sublayer and a second sublayer; the first sublayer includes Al a Nb b B 1-a-b N, 0.4≤a≤0.6, 0.3≤b≤0.55, 1-ab>0; the second sub-layer includes Al c Nb d W 1-c-d N, 0.4≤c≤0.6, 0.3≤d≤0.55, 1-cd>0; In some embodiments, the second deposition process satisfies one or more of the following conditions: The temperature of the substrate is 600℃-750℃; The bias voltage of the substrate is -60V to -120V; The target material for depositing the first sublayer includes an AlNbB alloy; in the AlNbB alloy, the atomic ratio of Al atoms, Nb atoms, and B atoms is (0.4-0.6):(0.3-0.55):(0.01-0.1). The average power for depositing the first sublayer is 2000W-6000W; The target material for depositing the second sublayer includes an AlNbW alloy; in the AlNbW alloy, the atomic ratio of Al atoms, Nb atoms, and W atoms is (0.4-0.6):(0.3-0.55):(0.01-0.1). The average power for depositing the second sublayer was 2000W-6000W; The second deposition process further includes introducing nitrogen gas at a flow rate of 200 sccm-500 sccm; The working pressure for the second deposition treatment is 0.4 Pa - 0.8 Pa; Counting from the side of the functional layer closest to the stress buffer layer towards the side closest to the surface layer, the average power of the second sublayer in the nth unit layer is greater than the average power of the second sublayer in the (n+1)th unit layer; where n+1≤N, and n and N are independent positive integers; Counting from the side of the functional layer closest to the stress buffer layer toward the side closest to the surface layer, the ratio of the average power of the first sublayer in the nth unit layer to the average power of the first sublayer in the (n+1)th unit layer is 1:(0.95-1.05).
[0158] Thus, in the plasma environment, sputtered AlNbB particles react with active nitrogen free radicals generated by nitrogen dissociation in the gas phase, thereby depositing a first sublayer; sputtered AlNbW particles react with active nitrogen free radicals generated by nitrogen dissociation in the gas phase, thereby depositing a second sublayer; and by controlling the deposition conditions of the second deposition process within the aforementioned range, a functional layer within the scope defined in this application can be obtained.
[0159] It is understandable that during the deposition of the second sublayer in each functional layer, the average power of pulsed magnetron sputtering gradually decreases, the plasma concentration gradually decreases, and the thickness of the second sublayer in the functional layer also gradually decreases.
[0160] As an example, the temperature of the substrate can be 600℃, 620℃, 640℃, 660℃, 680℃, 700℃, 720℃, 740℃, 750℃, or a range of any two of the above values.
[0161] As an example, the bias voltage of the substrate can be -60V, -65V, -70V, -75V, -80V, -85V, -90V, -95V, -100V, -105V, -110V, -115V, -120V, etc., or a range consisting of any two of the above values.
[0162] As an example, in the AlNbB alloy, the atomic ratio of Al atoms, Nb atoms, and B atoms can be 0.4:0.55:0.05, 0.45:0.5:0.05, 0.45:0.49:0.06, 0.5:0.45:0.05, 0.5:0.44:0.06, 0.5:0.4:0.1, 0.55:0.4:0.05, 0.55:0.39:0.06, 0.55:0.35:0.1, 0.6:0.35:0.05, 0.6:0.39:0.01, 0.6:0.3:0.1, etc., or a range consisting of any two of the above values.
[0163] As an example, the average power for depositing the first sublayer can be 2000W, 3000W, 4000W, 5000W, 6000W, or a range of any two of the above values.
[0164] As an example, in the AlNbW alloy, the atomic ratio of Al atoms, Nb atoms, and W atoms can be 0.4:0.55:0.05, 0.45:0.5:0.05, 0.45:0.49:0.06, 0.5:0.45:0.05, 0.5:0.44:0.06, 0.5:0.4:0.1, 0.55:0.4:0.05, 0.55:0.39:0.06, 0.55:0.35:0.1, 0.6:0.35:0.05, 0.6:0.39:0.01, 0.6:0.3:0.1, etc., or a range consisting of any two of the above values.
[0165] As an example, the average power for depositing the second sublayer can be 2000W, 3000W, 4000W, 5000W, 6000W, or a range of any two of the above values.
[0166] As an example, the flow rate of nitrogen gas can be 200 sccm, 250 sccm, 300 sccm, 350 sccm, 400 sccm, 450 sccm, 500 sccm, etc., or a range consisting of any two of the above values.
[0167] As an example, the working pressure of the second deposition process can be 0.4 Pa, 0.45 Pa, 0.5 Pa, 0.55 Pa, 0.6 Pa, 0.65 Pa, 0.7 Pa, 0.75 Pa, 0.8 Pa, or a range consisting of any two of the above values.
[0168] As an example, the ratio of the average power of the first sublayer in the nth unit layer to the average power of the first sublayer in the (n+1)th unit layer can be 1:0.95, 1:0.96, 1:0.97, 1:0.98, 1:0.99, 1:1.00, 1:1.01, 1:1.02, 1:1.03, 1:1.04, 1:1.05, or a range of any two of the above values.
[0169] S500, a third deposition process is performed on the side of the functional layer away from the stress buffer layer to obtain a surface layer; the surface layer includes Al. e Nb f B 1-e-f N, 0.4≤e≤0.6, 0.3≤f≤0.55, 1-ef>0.
[0170] In some embodiments, the third deposition process satisfies one or more of the following conditions: The temperature of the substrate is 600℃-750℃; The bias voltage of the substrate is -80V to -140V; The target material for depositing the surface layer includes an AlNbB alloy; in the AlNbB alloy, the atomic ratio of Al atoms, Nb atoms, and B atoms is (0.4-0.6):(0.3-0.55):(0.01-0.1). The average power of the third deposition process is 3000W-6000W; The third deposition process also includes introducing nitrogen gas at a flow rate of 200 sccm-500 sccm; The working pressure for the third deposition process is 0.4 Pa to 0.8 Pa.
[0171] Therefore, in the plasma environment, sputtered AlNbB particles react with active nitrogen free radicals generated by nitrogen dissociation in the gas phase, and then deposit to obtain the surface layer; and by controlling the deposition conditions of the third deposition process within the aforementioned range, the surface layer within the scope defined in this application can be obtained.
[0172] As an example, the temperature of the substrate can be 600℃, 620℃, 640℃, 660℃, 680℃, 700℃, 720℃, 740℃, 750℃, or a range of any two of the above values.
[0173] As an example, the bias voltage of the substrate can be -80V, -90V, -100V, -110V, -120V, -130V, -140V, etc., or a range consisting of any two of the above values.
[0174] As an example, in the AlNbB alloy, the atomic ratio of Al atoms, Nb atoms, and B atoms can be 0.4:0.55:0.05, 0.45:0.5:0.05, 0.45:0.49:0.06, 0.5:0.45:0.05, 0.5:0.44:0.06, 0.5:0.4:0.1, 0.55:0.4:0.05, 0.55:0.39:0.06, 0.55:0.35:0.1, 0.6:0.35:0.05, 0.6:0.39:0.01, 0.6:0.3:0.1, etc., or a range consisting of any two of the above values.
[0175] As an example, the average power of the third deposition process can be 3000W, 4000W, 5000W, 6000W, etc., or a range consisting of any two of the above values.
[0176] As an example, the flow rate of nitrogen gas can be 200 sccm, 250 sccm, 300 sccm, 350 sccm, 400 sccm, 450 sccm, 500 sccm, etc., or a range consisting of any two of the above values.
[0177] As an example, the working pressure of the third deposition process can be 0.4 Pa, 0.45 Pa, 0.5 Pa, 0.55 Pa, 0.6 Pa, 0.65 Pa, 0.7 Pa, 0.75 Pa, 0.8 Pa, etc., or a range consisting of any two of the above values.
[0178] In some embodiments, this application provides a method for preparing a composite coated cutting tool, which further includes: In step S100, a fourth deposition process is performed on at least one side of the substrate to obtain the adhesive layer, the adhesive layer comprising titanium metal.
[0179] In some embodiments, the fourth deposition process satisfies one or more of the following conditions: The temperature of the substrate is 600℃-750℃; The bias voltage of the substrate is -150V to -200V; The target material for depositing the adhesive layer includes titanium metal; The average power of the fourth deposition process is 6000W-8000W; The working pressure for the fourth deposition process is 0.4 Pa to 0.8 Pa. Before the fourth deposition process, the substrate is further cleaned; the cleaning process includes, in sequence, sandblasting, water washing, and glow discharge cleaning.
[0180] Therefore, in the plasma environment, the sputtered Ti is directly deposited on the substrate surface to form a binder layer; and by controlling the deposition conditions of the fourth deposition process within the aforementioned range, a binder layer within the scope defined in this application can be obtained.
[0181] Furthermore, impurity phases are inevitably present on the substrate surface during processing. Cleaning the substrate before deposition can effectively improve the adhesion strength between the substrate and the composite coating.
[0182] As an example, the temperature of the substrate can be 600℃, 620℃, 640℃, 660℃, 680℃, 700℃, 720℃, 740℃, 750℃, or a range of any two of the above values.
[0183] As an example, the bias voltage of the substrate can be -150V, -160V, -170V, -180V, -190V, -200V, etc., or a range consisting of any two of the above values.
[0184] As an example, the average power of the fourth deposition process can be 6000W, 7000W, 8000W, or a range of any two of the above values.
[0185] As an example, the working pressure of the fourth deposition process can be 0.4Pa, 0.45Pa, 0.5Pa, 0.55Pa, 0.6Pa, 0.65Pa, 0.7Pa, 0.75Pa, 0.8Pa, or a range consisting of any two of the above values.
[0186] In some embodiments, this application provides a method for preparing a composite coated cutting tool, which further includes: In step S200, a fifth deposition process is performed on the side of the adhesive layer away from the substrate to obtain the transition layer, which comprises TiN.
[0187] In some embodiments, the fifth deposition process satisfies one or more of the following conditions: The temperature of the substrate is 600℃-750℃; The bias voltage of the substrate is -100V to -150V; The target material for depositing the transition layer includes titanium metal; The average power of the fifth deposition process is 6000W-8000W; The fifth deposition process also includes introducing nitrogen gas at a flow rate of 200 sccm-300 sccm; The working pressure for the fifth deposition treatment is 0.4 Pa to 0.8 Pa.
[0188] Therefore, in the plasma environment, the sputtered Ti particles react with the active nitrogen free radicals generated by the dissociation of nitrogen gas in the gas phase, and then deposit a transition layer; and by controlling the deposition conditions of the fifth deposition process within the aforementioned range, a transition layer within the scope defined in this application can be obtained.
[0189] As an example, the temperature of the substrate can be 600℃, 620℃, 640℃, 660℃, 680℃, 700℃, 720℃, 740℃, 750℃, or a range of any two of the above values.
[0190] As an example, the bias voltage of the substrate can be -100V, -110V, -120V, -130V, -140V, -150V, etc., or a range consisting of any two of the above values.
[0191] As an example, the average power of the fifth product processing can be 6000W, 7000W, 8000W, etc., or a range consisting of any two of the above values.
[0192] As an example, the flow rate of nitrogen gas can be 200 sccm, 250 sccm, 300 sccm, or a range of any two of the above values.
[0193] As an example, the working pressure of the fifth deposition process can be 0.4 Pa, 0.45 Pa, 0.5 Pa, 0.55 Pa, 0.6 Pa, 0.65 Pa, 0.7 Pa, 0.75 Pa, 0.8 Pa, or a range consisting of any two of the above values.
[0194] In a third aspect, this application provides the application of the aforementioned composite coated tool or the composite coated tool prepared by the aforementioned method in the cutting of titanium alloys and / or high-temperature alloys.
[0195] In some embodiments, the titanium alloy includes one or both of TC4 and TC18.
[0196] TC4 and TC18 are alloy grades of titanium alloys; among them, the nominal chemical composition of TC4 is Ti-6Al-4V, and the nominal chemical composition of TC18 is Ti-5Al-4.75Mo-4.75V-1Cr-1Fe.
[0197] In some embodiments, the high-temperature alloy includes one or both of nickel-based and iron-based high-temperature alloys. As an example, the nickel-based high-temperature alloy may include one or both of Inconel 718 and Waspaloy.
[0198] The following specific embodiments illustrate the solution of this application. It should be noted that these embodiments are for illustrative purposes only and should not be considered as limiting the scope of this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0199] Example 1 The preparation of composite-coated cutting tools using high-power pulsed magnetron sputtering technology includes the following steps: S1. Using WC-Co cemented carbide as the substrate of the tool, the substrate is subjected to sandblasting and washing treatment in sequence; after drying, it is placed on a rotating frame and the surface of the substrate is subjected to glow discharge cleaning treatment. S2. Deposit a Ti binder layer on a clean substrate surface. The deposition process parameters are as follows: The substrate temperature was 650℃, the substrate bias voltage was -200V, the Ti target sputtering power was 8000W, the pressure was 0.6Pa, and the deposition time was 480s. The thickness of the Ti adhesive layer is 50 nm; S3. Deposit a TiN transition layer on the surface of the Ti binder layer. The deposition process parameters are as follows: The substrate temperature was 650℃, the substrate bias voltage was -150V, the Ti target sputtering power was 8000W, the N2 flow rate was 300sccm, the pressure was 0.6Pa, and the deposition time was 960s. The thickness of the TiN transition layer is 100 nm; S4. Deposit a stress buffer layer (Al) on the surface of the TiN transition layer. 0.6 Nb 0.4 (N layers), deposition process parameters are: The substrate temperature is 650℃, the substrate bias voltage is -40V, and Al... 0.6 Nb 0.4 The sputtering power of the target material was gradually increased from 1000W to 5000W, the N2 flow rate was 300sccm, the pressure was 0.6Pa, and the deposition time was 2400s; The stress buffer layer has a thickness of 0.5 μm; the average grain size is 100 nm; and the Vickers hardness is 26 GPa. S5. Deposit a functional layer (Al) on the surface of the stress buffer layer. 0.6 Nb 0.3 B 0.1 N layer and Al 0.6 Nb 0.3 W 0.1 (N layers are alternately set), where the deposition process parameters within a single cycle are: First sublayer: substrate temperature 650℃, substrate bias voltage -60V, Al 0.6 Nb 0.3 B 0.1 The sputtering power of the target is 6000W, the flow rate of N2 is 300sccm, and the pressure is 0.6Pa; Second sublayer: matrix temperature 650℃, matrix bias voltage -60V, N2 flow rate 300sccm, pressure 0.6Pa; This process repeats for a total of 80 cycles, from the first cycle to the 80th cycle. 0.6 Nb 0.3 W 0.1 The sputtering power of the target material was gradually reduced from 6000W to 2000W. The total deposition time was 7200s over 80 cycles. The total thickness of the functional layer is 3 μm; the average grain size is 30 nm; and the Vickers hardness is 32 GPa. S6. Deposit a surface layer (Al) on the functional layer surface. 0.6 Nb 0.3 B 0.1 (N layers), deposition process parameters are: The substrate temperature is 650℃, the substrate bias voltage is -80V, and Al... 0.6 Nb 0.3 B 0.1 The target sputtering power was constant at 6000W, the N2 flow rate was 300sccm, the pressure was 0.6Pa, and the deposition time was 2400s. The surface layer thickness is 0.5 μm; the average grain size is 20 nm; and the Vickers hardness is 36 GPa. S7. After deposition is complete, the temperature of the substrate is lowered to room temperature to obtain the composite coated tool.
[0200] Examples 2-6 The difference between Example 2 and Example 1 is as follows: The stress buffer layer is Al 0.5 Nb 0.5 N coating; In the functional layer, the first sub-layer is AI. 0.5 Nb 0.45 B0.05 N, the second sublayer is Al 0.5 Nb 0.45 W 0.05 N; The surface layer is Al. 0.5 Nb 0.45 B 0.05 N.
[0201] The difference between Example 3 and Example 1 is as follows: In the functional layer, the first sub-layer is AI. 0.6 Nb 0.35 B 0.05 N, the second sublayer is Al 0.6 Nb 0.35 W 0.05 N; The surface layer is Al. 0.6 Nb 0.35 B 0.05 N.
[0202] The difference between Example 4 and Example 1 is as follows: In the functional layer, the first sub-layer is AI. 0.6 Nb 0.37 B 0.03 N, the second sublayer is Al 0.6 Nb 0.38 W 0.02 N; The surface layer is Al. 0.6 Nb 0.37 B 0.03 N.
[0203] The difference between Example 5 and Example 1 is: The stress buffer layer is Al 0.4 Nb 0.6 N layers.
[0204] The difference between Example 6 and Example 1 is: In the functional layer, the first sub-layer is AI. 0.4 Nb 0.55 B 0.05 N, the second sublayer is Al 0.4 Nb 0.55 W 0.05 N; The surface layer is Al. 0.4 Nb 0.55 B 0.05 N.
[0205] Comparative Examples 1-8 The difference between Comparative Example 1 and Example 1 is that steps S2-S4 are omitted; that is, the composite coated tool does not contain an adhesive layer, a transition layer, or a stress buffer layer. The total thickness of Comparative Example 1 is the same as that of Example 1. Due to the lack of an adhesive layer, a transition layer, and a stress buffer layer, the missing thickness in the composite coating is compensated for by increasing the surface layer thickness.
[0206] The difference between Comparative Example 2 and Example 1 is that step S4 is omitted; that is, the composite coated tool does not contain a stress buffer layer. The total thickness of Comparative Example 2 is the same as that of Example 1. Due to the lack of a stress buffer layer, the missing thickness in the composite coating is compensated by increasing the surface layer thickness.
[0207] The difference between Comparative Example 3 and Example 1 is that step S5 is omitted; that is, the composite coated tool does not contain a functional layer. The total thickness of Comparative Example 3 is the same as that of Example 1. Due to the lack of a functional layer, the missing thickness in the composite coating is compensated by increasing the surface layer thickness.
[0208] The difference between Comparative Example 4 and Example 1 is that: in step S5, the sputtering power of the target material for the second sub-layer of each layer in the deposition functional layer is 6000W; the deposition time is adjusted, and the total thickness and deposition cycle of the functional layer in Comparative Example 4 are the same as those in Example 1.
[0209] The difference between Comparative Example 5 and Example 1 is that in step S5, the target material for depositing the first sublayer is Al. 0.6 Nb 0.4 That is, the first sub-layer is Al 0.6 Nb 0.4 N layers.
[0210] The difference between Comparative Example 6 and Example 1 is that in step S5, the target material for depositing the second sublayer is Al. 0.6 Nb 0.4 That is, the second sublayer is Al. 0.6 Nb 0.4 N layers.
[0211] The difference between Comparative Example 7 and Example 1 is that the functional layer is replaced with a CrAlN layer of equal thickness.
[0212] The difference between Comparative Example 8 and Example 1 is that the functional layer is replaced with a TiAlN layer of equal thickness.
[0213] Performance testing: (1) Hardness A diamond indenter is vertically pressed into the composite-coated tool, with the indentation direction from the composite coating surface towards the substrate. The loading force and indentation depth curve of the diamond indenter are recorded in real time, and the hardness value is calculated based on the indentation deformation after unloading.
[0214] (2) Bond strength between the substrate and the composite coating Using a diamond conical indenter, the coating is slid horizontally at a constant speed along the surface of the composite coating. The normal load increases linearly and continuously. The indenter generates shear stress, and the coating successively develops microcracks, peeling, interface detachment, and complete delamination. The load corresponding to the instant of coating cracking / peeling is the critical load Lc. The higher the value of Lc, the stronger the coating adhesion and the better the scratch resistance.
[0215] (3) Coefficient of friction Using a friction testing machine, a cemented carbide ball is continuously slid back and forth or unidirectionally on the surface of a composite coating under constant pressure and a fixed sliding speed; the equipment collects the friction force in real time, thereby calculating the coefficient of friction.
[0216] (4) Cutting edge wear Material to be cut: Titanium alloy TC18; The composite coated cutting tools in the examples or comparative examples were prepared according to specification SCGT 120630-MR4. Specifically, SCGT120630-MR4 refers to a cutting tool obtained by sequentially performing face milling, slot milling, ramp milling, helical interpolation milling, plunge milling, and cavity milling steps, resulting in a cutting tool with the insert shape designated S, a cutting tip radius of 3mm, an insert inscribed circle of 12.7mm, an insert thickness of 6.35mm, an insert clearance angle of 7°, and an inner bore diameter of 5.6mm.
[0217] Cutting conditions: cutting speed 40m / min, feed 0.6mm / z, depth of cut 1.5mm, wet cutting; The wear amount VB (in mm) of the composite coated cutting tools obtained in the examples and comparative examples was measured on the cutting surface after cutting titanium alloys for different times.
[0218] The wear amount VB of the cutting tool face was measured using an OLYMPUS SZ61 optical ultra-depth-of-field microscope with a graduated scale.
[0219] The test results of the examples and comparative examples are shown in Table 1.
[0220] Table 1
[0221] Note: When the cutting wear exceeds 0.3mm, the tool is considered to have failed. In Table 1, "--" indicates that the cutting wear of the tool exceeds 0.3mm, and the tool has failed.
[0222] As shown in Table 1, compared with the comparative example, the composite coated tool prepared in the embodiments of this application has better overall performance. Under the same substrate and cutting conditions, the cutting performance of the composite coated tool of this application is better than that of the comparative example.
[0223] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A composite coated cutting tool, characterized in that, Includes a substrate and a composite coating located on at least one side of the substrate; The composite coating includes: Adhesive layer; the adhesive layer is located on at least one side of the substrate; Transition layer; the transition layer is located on the side of the adhesive layer away from the substrate; Stress buffer layer; the stress buffer layer is located on the side of the transition layer away from the adhesive layer; the stress buffer layer includes Al x Nb 1-x N, 0.4 ≤ x ≤ 0.6; Functional layer; the functional layer is located on the side of the stress buffer layer away from the transition layer; the functional layer comprises N unit layers, N≥2; each unit layer comprises a first sub-layer and a second sub-layer; the first sub-layer comprises A1 a Nb b B 1-a-b N, 0.4≤a≤0.6, 0.3≤b≤0.55, 1-ab>0; the second sub-layer includes Al c Nb d W 1-c-d N, 0.4≤c≤0.6, 0.3≤d≤0.55, 1-cd>0; Surface layer; the surface layer is located on the side of the functional layer away from the stress buffer layer; the surface layer includes Al e Nb f B 1-e- f N, 0.4≤e≤0.6, 0.3≤f≤0.55, 1-ef>0.
2. The composite coated cutting tool according to claim 1, characterized in that, One or more of the following conditions must be met: 0.01 ≤ 1 - ab ≤ 0.1; 0.01≤1-cd≤0.1; 0.01≤1-ef≤0.
1.
3. The composite coated cutting tool according to claim 2, characterized in that, The unit layer satisfies one or more of the following conditions: The thickness of a single unit layer is 10nm-50nm; The thickness of the first sublayer is 5nm-25nm; The thickness of the second sublayer is 5nm-25nm; Counting from the side of the functional layer closest to the stress buffer layer towards the side closest to the surface layer, the thickness of the second sub-layer in the nth unit layer is greater than the thickness of the second sub-layer in the (n+1)th unit layer, where n+1≤N, and n and N are independent positive integers; Counting from the side of the functional layer closest to the stress buffer layer towards the side closest to the surface layer, the ratio of the thickness of the first sub-layer in the nth unit layer to the thickness of the first sub-layer in the (n+1)th unit layer is 1:(0.95-1.05). The N is greater than or equal to 6 and less than or equal to 200.
4. The composite coated cutting tool according to any one of claims 1-3, characterized in that, The stress buffer layer has a face-centered cubic crystal structure.
5. The composite coated cutting tool according to any one of claims 1-3, characterized in that, One or two of the following conditions must be met: The average grain size of the grains in the stress buffer layer is greater than the average grain size of the grains in the functional layer, which is greater than the average grain size of the grains in the surface layer. The Vickers hardness of the stress buffer layer is less than that of the functional layer, which in turn is less than that of the surface layer.
6. The composite coated cutting tool according to claim 5, characterized in that, One or more of the following conditions must be met: The average grain size of the grains in the stress buffer layer is 30nm-200nm; The average grain size of the grains in the functional layer is 5nm-50nm; The average grain size of the grains in the surface layer is 10nm-30nm; The Vickers hardness of the stress buffer layer is 24 GPa-32 GPa; The Vickers hardness of the functional layer is 26 GPa-36 GPa; The Vickers hardness of the surface layer is 27 GPa-38 GPa.
7. The composite coated cutting tool according to any one of claims 1-3, characterized in that, One or more of the following conditions must be met: The thickness of the stress buffer layer is 0.2μm-1.0μm; The thickness of the functional layer is 0.5μm-3.0μm; The thickness of the surface layer is 0.5μm-2.0μm.
8. The composite coated cutting tool according to any one of claims 1-3, characterized in that, The adhesive layer satisfies one or two of the following conditions: The adhesive layer comprises titanium metal; The thickness of the adhesive layer is 0.05μm-0.1μm.
9. The composite coated cutting tool according to claim 8, characterized in that, The transition layer satisfies one or two of the following conditions: The transition layer comprises TiN; The thickness of the transition layer is 0.1μm-0.2μm.
10. The composite coated cutting tool according to any one of claims 1-3, characterized in that, The thickness of the composite coating is 1.5μm-5.0μm.
11. The composite coated cutting tool according to any one of claims 1-3, characterized in that, The matrix satisfies one or two of the following conditions: The matrix includes one or more of cemented carbide, cermet, cubic boron nitride sintered body, and high-speed steel; The matrix comprises a tungsten carbide cemented carbide doped with cobalt metal, wherein the mass percentage of cobalt is 6%-12% based on the mass of the cobalt-doped tungsten carbide cemented carbide.
12. A method for preparing a composite-coated cutting tool, characterized in that, include: A composite coating is deposited on at least one side of the substrate; The deposited composite coating includes: An adhesive layer is deposited on at least one side of the substrate; A transition layer is deposited on the side of the adhesive layer away from the substrate; A first deposition process is performed on the side of the transition layer away from the adhesive layer to obtain a stress buffer layer; A second deposition process is performed on the side of the stress buffer layer away from the transition layer to obtain a functional layer containing N unit layers, where N≥2; A third deposition process is performed on the side of the functional layer away from the stress buffer layer to obtain the surface layer; The stress buffer layer includes Al x Nb 1-x N, 0.4 ≤ x ≤ 0.6; The unit layer in the functional layer includes a first sub-layer and a second sub-layer; the first sub-layer includes A1 a Nb b B 1-a-b N, 0.4≤a≤0.6, 0.3≤b≤0.55, 1-ab>0; the second sub-layer includes Al c Nb d W 1-c-d N, 0.4≤c≤0.6, 0.3≤d≤0.55, 1-cd>0; The surface layer includes Al e Nb f B 1-e-f N, 0.4≤e≤0.6, 0.3≤f≤0.55, 1-ef>0.
13. The method according to claim 12, characterized in that, The method for depositing the composite coating includes physical vapor deposition; the physical vapor deposition method includes pulsed magnetron sputtering, wherein the average power of the pulsed magnetron sputtering is 1000W-10000W.
14. The method according to claim 12 or 13, characterized in that, The second deposition process satisfies one or more of the following conditions: The temperature of the substrate is 600℃-750℃; The bias voltage of the substrate is -60V to -120V; The target material for depositing the first sublayer includes an AlNbB alloy; in the AlNbB alloy, the atomic ratio of Al atoms, Nb atoms, and B atoms is (0.4-0.6):(0.3-0.55):(0.01-0.1). The average power for depositing the first sublayer is 2000W-6000W; The target material for depositing the second sublayer includes an AlNbW alloy; In the AlNbW alloy, the atomic ratio of Al atoms, Nb atoms, and W atoms is (0.4-0.6):(0.3-0.55):(0.01-0.1). The average power for depositing the second sublayer was 2000W-6000W; The second deposition process further includes introducing nitrogen gas at a flow rate of 200 sccm-500 sccm; The working pressure for the second deposition treatment is 0.4 Pa - 0.8 Pa; Counting from the side of the functional layer closest to the stress buffer layer towards the side closest to the surface layer, the average power of the second sublayer in the nth unit layer is greater than the average power of the second sublayer in the (n+1)th unit layer; where n+1≤N, and n and N are independent positive integers; Counting from the side of the functional layer closest to the stress buffer layer toward the side closest to the surface layer, the ratio of the average power of the first sublayer in the nth unit layer to the average power of the first sublayer in the (n+1)th unit layer is 1:(0.95-1.05).
15. The method according to claim 12 or 13, characterized in that, The first deposition process satisfies one or more of the following conditions: The temperature of the substrate is 600℃-750℃; The bias voltage of the substrate is -40V to -100V; The target material for depositing the stress buffer layer includes an AlNb alloy; in the AlNb alloy, the atomic ratio of Al atoms to Nb atoms is (0.4-0.6):(0.6-0.4); The average power of the first deposition process is 1000W-6000W; During the first deposition process, the power gradually increases from 1000W to h, where h ranges from 2000W to 6000W. The first deposition process further includes introducing nitrogen gas at a flow rate of 200 sccm-500 sccm; The working pressure of the first deposition treatment is 0.4 Pa to 0.8 Pa.
16. The method according to claim 12 or 13, characterized in that, The third deposition process satisfies one or more of the following conditions: The temperature of the substrate is 600℃-750℃; The bias voltage of the substrate is -80V to -140V; The target material for depositing the surface layer includes an AlNbB alloy; in the AlNbB alloy, the atomic ratio of Al atoms, Nb atoms, and B atoms is (0.4-0.6):(0.3-0.55):(0.01-0.1). The average power of the third deposition process is 3000W-6000W; The third deposition process also includes introducing nitrogen gas at a flow rate of 200 sccm-500 sccm; The working pressure for the third deposition process is 0.4 Pa to 0.8 Pa.
17. The method according to claim 12 or 13, characterized in that, Also includes: A fourth deposition process is performed on at least one side of the substrate to obtain the adhesive layer, the adhesive layer comprising titanium metal; The fourth deposition process satisfies one or more of the following conditions: The temperature of the substrate is 600℃-750℃; The bias voltage of the substrate is -150V to -200V; The target material for depositing the adhesive layer includes titanium metal; The average power of the fourth deposition process is 6000W-8000W; The working pressure for the fourth deposition process is 0.4 Pa to 0.8 Pa. Prior to the fourth deposition process, the substrate is also cleaned. The cleaning process includes, in sequence: sandblasting, water washing, and glow discharge cleaning.
18. The method according to claim 17, characterized in that, Also includes: A fifth deposition process is performed on the side of the adhesive layer away from the substrate to obtain the transition layer, the transition layer comprising TiN; The fifth deposition process satisfies one or more of the following conditions: The temperature of the substrate is 600℃-750℃; The bias voltage of the substrate is -100V to -150V; The target material for depositing the transition layer includes titanium metal; The average power of the fifth deposition process is 6000W-8000W; The fifth deposition process also includes introducing nitrogen gas at a flow rate of 200 sccm-300 sccm; The working pressure for the fifth deposition treatment is 0.4 Pa to 0.8 Pa.
19. The application of a composite coated tool as described in any one of claims 1-11 or a composite coated tool prepared by the method described in any one of claims 12-18 in the cutting of titanium alloys and / or high-temperature alloys.
20. The application according to claim 19, characterized in that, One or two of the following conditions must be met: The titanium alloy includes one or both of TC4 and TC18; The high-temperature alloy includes one or both of nickel-based and iron-based high-temperature alloys.